2005
DOI: 10.1111/j.1365-2125.2005.02452.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐factor Xa kinetics after intravenous enoxaparin in patients undergoing percutaneous coronary intervention: a population model analysis

Abstract: AimRecent studies have suggested that intravenous (i.v.) enoxaparin could be used as antithrombotic therapy in patients ongoing percutaneous coronary intervention (PCI). However, anti-Xa pharmacokinetics following different i.v. dosing regimens is not clearly established. MethodsA population pharmacokinetic analysis was developed using anti-Xa activities measured in 546 patients who received a single 0.5 mg kg -1 i.v. dose of enoxaparin immediately before PCI. Effects of higher doses (0.75 mg kg -1 and 1 mg kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
22
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
6
22
0
1
Order By: Relevance
“…26 Thus, body weight-adjusted dosing does appear to be more useful. All these effects imply that enoxaparin may be a more reliable and predictable alternative to UFH; however, comparing anticoagulation effects for these heparins is difficult.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…26 Thus, body weight-adjusted dosing does appear to be more useful. All these effects imply that enoxaparin may be a more reliable and predictable alternative to UFH; however, comparing anticoagulation effects for these heparins is difficult.…”
Section: Discussionmentioning
confidence: 97%
“…25 When given intravenously, enoxaparin at 0.5 mg/kg reaches a desired anticoagulation for only up to 2 hours. 26 In the current study, the mean body weight-adjusted dose of UFH was 69.4 Ϯ 12.7 IU/kg for all patients. The body weight-adjusted doses of heparin for the three patients with bleeding complications were 62.5, 71, and 74 IU/kg and thus well within the suggested range for optimal anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that an SQ upstream treatment by enoxaparin at the dose of 1 mg/kg twice daily (0.65 mg/kg twice daily for patients with impaired renal function) allows adequate anticoagulation for PCI within 8 h of the last injection, whereas an additional IV bolus of 0.25 to 0.30 mg/kg is needed (13,15,16) if the last SQ was injected more than 8 h and less than 12 h before the procedure. Our work confirms that this enoxaparin dose regimen is associated with an anti-Xa activity in the therapeutic range (0.5 to 1.8 IU/ml) in the large majority of patients (95%) with low rates of under-or over-anticoagulated patients (4% and 1%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A simulated study based on the kinetics of F Xa inhibition after 0.5 mg/kg i.v. dose of enoxaparin [17] reported that after the i.v. dose of 0.75 mg/kg applied before PCI, the anticoagulation effects of enoxaparin >0.5 IU/ml persisted for 3.4±1.1 h and 28% of patients achieved initial inhibition higher than 1.8 IU/ml [13,14].…”
Section: Discussionmentioning
confidence: 99%